2015
DOI: 10.1039/c5ra01722j
|View full text |Cite
|
Sign up to set email alerts
|

Cross-linked protein crystals by glutaraldehyde and their applications

Abstract: Cross-linked protein crystal technology, as either a protein stabilisation or enzyme immobilisation method, has garnered more attention recently. This method not only can retain the original activity of the protein molecule but can also significantly enhance the crystals' mechanical and chemical stability. This review presents the preparation and mechanism of cross-linked protein crystals using glutaraldehyde. The mechanical, chemical and thermal properties of the cross-linked protein crystals are also reviewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 115 publications
0
48
0
Order By: Relevance
“…It was observed that the TSM value was the lowest for the 20% GD film. This can be correlated with the type of chemical cross‐links formed by GD with polypeptide chains that results in a change of the solubility of CEPI in water. Initially, GD reacts with the amino acid groups that are easily accessible or present in the outer side of the protein structure.…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that the TSM value was the lowest for the 20% GD film. This can be correlated with the type of chemical cross‐links formed by GD with polypeptide chains that results in a change of the solubility of CEPI in water. Initially, GD reacts with the amino acid groups that are easily accessible or present in the outer side of the protein structure.…”
Section: Resultsmentioning
confidence: 99%
“…Crosslinked enzymes were the first proposal, but the reproducibility was not simple, and enzyme activity losses by chemical modification were significant (Cao and others ; Sheldon ; Ghafourifar and others ). The crosslinked enzyme crystals (CLECs) (Clair and Navia ; Khalaf and others ; St. Häring and Schreier ; Yan and others ) yielded better results, and later the strategy was simplified through the concept of crosslinked enzyme aggregates (CLEAs). CLEAs formation is an immobilization alternative with good acceptance in academia (Cao and others ; Sheldon and others ; Sheldon ; Sheldon, ) (Figure ).…”
Section: Improving Proteases For Biotechnology Applicationsmentioning
confidence: 99%
“…Soon after, they demonstrated the enzymatic activity of GA cross‐linked carboxypeptidase‐A crystals in aqueous solutions different from that of the crystallization environment (Quiocho & Richards, ). Since then, aldehydes (Figure a), specifically GA, have been the dominant cross‐linking agents for the stabilization of protein crystals (Cohen‐Hadar et al, ; N. K. Khalaf et al, ; Yan et al, ). Despite the ubiquity of GA cross‐linking, the chemical basis is incompletely understood.…”
Section: Protein Crystalsmentioning
confidence: 99%